Avaliação comparativa do desempenho térmico de módulos executados em light steel frame com cobertura verde e com telhas de fibrocimento - Costa, Angélica Felicidade Guião Marcato (2017)
This research aimed to compare the thermal performance provided in experimental modules, one of these was performed with conventional cover, made of asbestos cement tiles, and another with green cover. As an experimental research proposal of methodology, we sought alternatives of a sustainable nature to elaborate the studied modules, opting for the use of dry construction in Light Steel Frame. From the construction of the modules, in a wide place and without the interference of shading, measuring instruments were installed in the inner part of themselves, where the of air temperature and relative humidity were collected. From the data, representative episodes were determined for the studies, which were evaluated for the degree of thermal comfort provided to the modules by the cover systems under study. As a result, it was observed that the module with green roof had better performance than the module with conventional cover, in all the selected episodes, maintaining with lower internal temperature fluctuation throughout the days, indicating that the green roof has characteristic Thermal insulation, reducing the heat flow from the roof.